Regulation of skeletal muscle amino acid metabolism during exercise - Gibala, M. J. (International Journal of Sport Nutrition and Exercise Metabolism, 2001)
The contribution of amino acid oxidation to total energy expenditure is negligible during short-term intense exercise and accounts for 3Ð6% of the total adenosine triphosphate supplied during prolonged exercise in humans. While not quantitatively important in terms of energy supply, the intermediary metabolism of several amino acidsÑnotably glutamate, alanine, and the branched-chain amino acidsÑaffects other metabolites, including the intermediates within the tricarboxylic acid (TCA) cycle. Glutamate appears to be a key substrate for the rapid increase in muscle TCA cycle intermediates (TCAI) that occurs at the onset of moderate to intense exercise, due to a rightward shift of the reaction catalyzed by alanine aminotransferase (glutamate + pyruvate <-> alanine + 2-oxoglutarate). The pool of muscle TCAI declines during prolonged exercise, and this has been attributed to an increase in leucine oxidation that relies on one of the TCAI. However, this mechanism does not appear to be quantitatively important due of the relatively low maximal activity of branched-chain oxoacid dehydrogenase, the key enzyme involved. It has been suggested that an increase in TCAI is necessary to attain high rates of aerobic energy production and that a decline in TCAI may be a causative factor in local muscle fatigue. These topics remain controversial, but recent evidence suggests that changes in TCAI during exercise are unrelated to oxidative energy provision in skeletal muscle.